Evaluasi UI/UX Pada Website Promosi UD Rizky Ananta Menggunakan System Usability Scale (SUS) - Nur h, Alfina; Widjiyati , Nur; Pramono , Eko; Andri , Rum; Ikmah , Ikmah; Sumiyanto , Ahmad (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
This study aims to evaluate the User Interface (UI) and User Experience (UX) of the UD Rizky Ananta promotional website using the System Usability Scale (SUS). The SUS method provides a quantitative assessment of usability and user satisfaction, while also identifying areas for improvement to enhance the overall user experience. Data were collected through a questionnaire consisting of 10 items distributed via Google Forms, using a convenience sampling method to reach easily accessible respondents. The author hopes that the results of this study can serve as a reference for improving and developing the UD Rizky Ananta promotional website. The SUS evaluation in this research yielded an average final score of 74.03, indicating that the website falls within the